Effect of Water Flooding on the Oviposition Capacity of Engorged Adult Females and Hatchability of Eggs of Dog Ticks: Rhipicephalus sanguineus and Haemaphysalis leachi leachi. (3rd April 2011) - Adejinmi, Johnson O.
Abstract : Effects of water flooding on the oviposition capacity of engorged adult females and hatchability of eggs of Rhipicephalus sanguineus and Haemaphysalis leachi leachi under laboratory conditions were investigated. The durations of time of water flooding were 1, 2, 4, 6, 12, 24, 48, 72, 96, and 120 hours. Engorged females of R. sanguineus and H. leachi leachi did not oviposit after being flooded for more than 48 and 6 hours, respectively. The preoviposition periods of both species were longer than those of their controls. The number of eggs laid were significantly lower (P < .05 ) and higher (P < .05 ) than their controls, respectively, for R. sanguineus and H. leachi leachi flooded for 1–4 hours. The hatchability of eggs of both species decreased as flooding time increased. The percentage of hatchability was negatively correlated with flooding time and was highly significant (r = - 0.97 ; P < .10 ). It is concluded that R. sanguineus tolerated simulated water flooding more than H. leachi leachi .